Colonic Adenocarcinoma at Advanced Stage in Adolescence: Report of 2 Cases - Divya S. Vundamati; Xiuxu Chen; Vivekanand Singh (Case Reports in Pathology)
Background. Carcinoma of colon is rare in children and adolescents. The staging criteria of the carcinoma is the same as those for adults. However, the pathogenetic background in pediatric cases is different from adults and usually involves mismatch repair gene mutations or familial polyposis syndromes. Case report. We describe two adolescents diagnosed with advanced stage colon carcinoma and discuss the histological appearance, testing for mismatch repair genes and contrast- it with carcinoma occurring in the setting of familial polyposis syndrome. Conclusion. Colonic carcinoma occurring in pediatric patients should prompt a work-up for mismatch repair gene mutation status. Despite higher stage of presentation, some of the pediatric patients may respond favorably to chemotherapy and surgical resection.